2020
DOI: 10.1021/acs.jpcc.0c00400
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Correlation between Stability, Fluxionality, and Absorption Spectra of Ultrasmall CdSe Clusters: A Computational Study

Abstract: Various properties of (CdSe) 3n clusters (n = 1−9) were obtained using computational techniques. Using a simple force field, a simulated annealing technique was employed to explore the potential energy landscape and identify the isomers available at low temperatures. The lowest energy isomer was then optimized using density functional theory, and the quantities associated with their stability and optoelectronics were calculated. The possibility of fluxionality for a given range of temperatures and solvents was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The initial structures of the CdSe QDs are extracted from previous studies. Five sizes are considered in our simulations, (CdSe) N of N = 6, 13, 19, 25, and 34 with diameters of 0.50, 0.85, 1.10, 1.20, and 1.40 nm, respectively. Considering the controversy on the most stable structures of (CdSe) 25 and (CdSe) 34 , ,, several more isomers for both QDs are collected and sent to structure relaxation.…”
Section: Computational Models and Methodsmentioning
confidence: 99%
“…The initial structures of the CdSe QDs are extracted from previous studies. Five sizes are considered in our simulations, (CdSe) N of N = 6, 13, 19, 25, and 34 with diameters of 0.50, 0.85, 1.10, 1.20, and 1.40 nm, respectively. Considering the controversy on the most stable structures of (CdSe) 25 and (CdSe) 34 , ,, several more isomers for both QDs are collected and sent to structure relaxation.…”
Section: Computational Models and Methodsmentioning
confidence: 99%
“…As the macroscopic properties of materials are generally determined by their microscopic structures, it is crucial to have a comprehensive understanding of the low-energy structures of CdSe clusters of different sizes. This has garnered significant attention in both experiment and theory during the past several years. …”
mentioning
confidence: 99%
“…This involves performing GO in an energy landscape defined by interatomic potentials, followed by refining the obtained low-energy structures at a higher level of theory, such as DFT. In recent years, prescreening has been used to explore the low-energy structures of CdSe clusters. ,,,, For example, Farrow and co-workers employed an evolutionary algorithm to search both directly and after prescreening on the DFT energy landscape for (CdSe) N ( N = 1–12) and observed a transition from two-dimensional rings to three-dimensional structures as N increases . Nguyen and co-workers adopted a combination of structural enumeration, Monte Carlo search, and local optimization to study (CdSe) N ( N = 1–37) and identified spheroidal, tubular, cage-core, and wurtzite structures for different values of N . , Tan and co-workers employed the ab initio random structure searching (AIRSS) method to investigate the structures of (CdSe) N ( N = 2–34) and found the clusters gradually transformed from cage-like to bulk-like structures as N increased .…”
mentioning
confidence: 99%
See 2 more Smart Citations